The Effect of Board of Directors' Diversity on Financial Distress in Energy Companies in Indonesia - Rangga Dhia Majduddin; Sri Widyaningsih; Hidayatul Nikmah (Telaah Bisnis, 2024)
The purpose of this study is to determine the role of board diversity in the form of the presence of female directors, the presence of foreign directors, the age of directors and the size of the board of directors against the risk of financial distress by conducting logistic regression testing on energy sector companies in Indonesia during 2018-2022. The results showed that the presence of female directors and the size of the board of directors negatively affected the risk of financial distress. Further research can test separately the period before the pandemic and after the pandemic so that the characteristics of each can be known in more detail. In addition, it can add cognitive diversity factors  such as education, expertise and tenure of directors. This research can be used as a reference to determine non-financial factors that can affect the possibility of financial distress experienced by the company.